2020
DOI: 10.3390/molecules25122826
|View full text |Cite
|
Sign up to set email alerts
|

High-CO2 Modified Atmosphere Packaging with Superchilling (−1.3 °C) Inhibit Biochemical and Flavor Changes in Turbot (Scophthalmus maximus) during Storage

Abstract: The effects of modified atmosphere packaging (MAP) in combination with superchilling (−1.3 °C) on the physicochemical properties, flavor retention, and organoleptic evaluation of turbot samples were investigated during 27 days storage. Results showed that high-CO2 packaging (70% or 60% CO2) combined with superchilling could reduce the productions of off-flavor compounds, including total volatile basic nitrogen (TVB-N) and ATP-related compounds. Twenty-four volatile organic compounds were determined by gas chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Similar results were reported in a study of rainbow trout fillets [13]. The storage temperature can directly affect the deterioration rate of aquatic products and the combination of MAP and superchilling can significantly improve product quality [14]. Some researchers studied the preservation effect of MAP (60% CO 2 /40% N 2 ) on fresh Atlantic salmon fillets at −2 • C and 4 • C. It was revealed that the quality of MAP salmon fillets deteriorated slowly at superchilling storage, which could effectively maintain the good quality of salmon fillets for 24 days [15].…”
Section: Introductionsupporting
confidence: 88%
“…Similar results were reported in a study of rainbow trout fillets [13]. The storage temperature can directly affect the deterioration rate of aquatic products and the combination of MAP and superchilling can significantly improve product quality [14]. Some researchers studied the preservation effect of MAP (60% CO 2 /40% N 2 ) on fresh Atlantic salmon fillets at −2 • C and 4 • C. It was revealed that the quality of MAP salmon fillets deteriorated slowly at superchilling storage, which could effectively maintain the good quality of salmon fillets for 24 days [15].…”
Section: Introductionsupporting
confidence: 88%
“…Sørensen, et al [ 47 ] studied the effect of sub-chilled storage at −1.7 °C in combination with MAP (40% CO 2 :60% N 2 ) on Atlantic cod and reported a sensory shelf life of more than 32 days. Moreover, Mei et al [ 48 ] demonstrated that turbot in MAP (60% CO 2 :30% N 2 :10% O 2 ) stored at sub-chilled conditions (−1.3 °C) maintained its freshness and prolonged the shelf life.…”
Section: Resultsmentioning
confidence: 99%
“…Total volatile basic nitrogen (TVB-N) values were measured by referring to the method recommended by Mei et al ( 32 ). Five grams of minced large yellow croaker samples were accurately weighed into a Kjeldahl nitrogen flask and mixed with 1.5 g of MgO.…”
Section: Methodsmentioning
confidence: 99%